Model-fitting approach to kinetic analysis of non-isothermal pyrolysis of pure and crude glycerol. (January 2020) - Almazrouei, Manar; Janajreh, Isam
Abstract: The pyrolysis of pure and crude glycerol from a transesterification process of waste cooking oil to biodiesel was investigated using thermogravimetric analysis. Unlike the pure glycerol that shows a single mass drop, there were five distinct phases in the pyrolysis of crude glycerol. Pure glycerol decomposed completely within the temperature range from (133–158) to (240–279) °C depending on the heating rate. Leaving behind a small mass fraction (less than 1%) of pyrolysis residues. However, the crude glycerol is more thermally stable over the second and third decomposition phases range from (138–151) to (357–401) °C leaving a large mass fraction of residue (∼12–13%). Model fitting methods of the Direct Differential and Coats-Redfern methods were used to evaluate non-isothermal kinetic parameters in the second phase using 24 reaction models. The activation energy obtained by compensation effect of direct differential method and Coats-Redfern method were (82.611 kJ/mol and 74.890 kJ/mol) and (74.253 kJ/mol and 58.281 kJ/mol) for the pure and crude glycerol, respectively. The best reaction models obtained by the highest R 2 and the master plot. The reaction order was calculated by Avrami theory, and the average value of 0.918 and 1.317 was obtained for the pure and crude glycerol, respectively. Highlights: Thermogravimetric analysis of pure and crude glycerol in TGA. Activation energy (E) of decomposition is calculated via model fitting methods. Compensation effect between activation energy and pre-exponential factor is found. Master plot method is used to determine the kinetic model. Reaction order is another critical parameter that is obtained by Aveami theory.